Challenges in Research Policy Evidence-Based Policy Briefs with Recommendations - Sivertsen, Gunnar; Langfeldt, Liv.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access volume addresses major challenges in research policy and provides advice on how to approach them. With chapters designed as accessible policy briefs, the book serves as an essential resource for new actors in research policy. It offers evidence-based recommendations on approaching research governance, funding, and evaluation challenges by covering these topics: Identifying and facilitating high quality research Evaluating transdisciplinary research quality Evaluating societal impact The dilemmas of grant peer review How citations relate to research quality Reforming research assessment The use of metrics in academic recruitment Quality criteria and concentration of research funding Balancing basic and external research funding Designing performance-based research funding systems Strategic steering of research at universities The consequences of paying to publish Each chapter combines research with practical advice and provides an overview of the state-of-the-art in research on the specific topic, as well as references for further reading.
Chapter 1. Introduction -- Part I: Notions of Research Quality and Evaluation of Research -- Chapter 2. Identifying and Facilitating High Quality Research -- Chapter 3. Evaluating Transdisciplinary Research Quality -- Chapter 4. Evaluating and Improving the Societal Impact of Research -- Chapter 5. The Many Dilemmas of Grant Peer Review -- Chapter 6. How Citations Relate to Research Quality -- Chapter 7. The Ongoing Reform of Research Assessment -- Chapter 8. The Use of Metrics in Academic Recruitment -- Part II: Research Funding and Governance -- Chapter 9. Quality Criteria and Concentration of Research Funding -- Chapter 10. Balancing Basic and External Research Funding: a Comparative Analysis -- Chapter 11. Designing Performance-based Research Funding Systems -- Chapter 12. The Limits of Universities$1 (BStrategic Capacity for Steering Research -- Chapter 13. The Consequences of Paying to Publish.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Political science; Education, Higher; Education and state; Political planning; Governance and Government; Higher Education; Education Policy; Policy Evaluation; Policy Implementation; Educational Policy and Politics